The clinical efficacy and safety research of Lianhuaqingwen (LHQW) in treatment of COVID-19: A systematic review and meta-analysis - Ling Fang; Yi Zhan; Liping Qu; Huafang Sheng (Elsevier, 2022)
Background: Although vaccines have been launched, COVID-19 has not been effectively curbed, and the number of infections is increasing. Compared with western medicine, Traditional Chinese Medicine has made some achievements in the treatment of COVID-19, which should be paid attention to and play a greater role. As a classical Chinese medicine prescription for treating pestilence, Lianhuaqingwen (LHQW) has gone to many countries with the Chinese medical team to participate in the local fight against the epidemic, which has been widely recognized. Methods: We searched MEDLINE, EMBASE, AMED, Chchrane Central Register of Controlled Trials (CENTRAL), PubMed, Web of Science, Chinese National Knowledge Infrastructure (CNKI), VIP Information Database (VIP), Chinese Biomedical Literature Database (CBM), and Wanfang Database from inception up to November 24, 2021, which formed the basis for evidence used to formulate recommendations. Sixteen randomized controlled trials (RCTs) involving 1896 patients were enrolled. LHQW is a traditional Chinese medicine compound preparation, which contains 13 traditional Chinese medicine (TCM) components. Two dosage formulations of LHQW were included: granule and capsule. The most commonly used dosage formulation was granule (15/17, 88.24%), followed by capsule (2/17, 11.76%). Conclusion: This systematic review and Meta analysis suggested that, in the treatment of COVID-19, LHQW Capsule (Granule) could not only significantly improve the fever symptoms, shorten the fever time, but also reduce the cough and fatigue symptoms, improve the clinical efficiency, improve the lung CT, significantly reduce the number of patients with mild to severe diseases, and have certain anti-inflammatory effect. And there is no server adverse events which support the safety of LHQW Capsule (Granule) for the treatment of COVID-19. As a classic formula of TCM, LHQW Capsule (Granule) could be used as potential candidates for COVID-19 in this battle.